Additive engineering for efficient wide-bandgap perovskite solar cells with low open-circuit voltage losses - Yu, Xixi; He, Huxue; Hui, Yunuo; Wang, Hua; Zhu, Xing; Li, Shaoyuan; Zhu, Tao (Frontiers in Chemistry, 2024)
High-performance wide-bandgap (WBG) perovskite solar cells are used as top cells in perovskite/silicon or perovskite/perovskite tandem solar cells, which possess the potential to overcome the Shockley-Queisser limitation of single-junction perovskite solar cells (PSCs). However, WBG perovskites still suffer from severe nonradiative recombination and large open-circuit voltage (Voc) losses, which restrict the improvement of PSC performance. Herein, we introduce 3,3'-diethyl-oxacarbo-cyanine iodide (DiOC2(3)) and multifunctional groups (C=N, C=C, C-O-C, C-N) into perovskite precursor solutions to simultaneously passivate deep level defects and reduce recombination centers. The multifunctional groups in DiOC2(3) coordinate with free Pb 2+ at symmetric sites, passivating Pb vacancy defects, effectively suppressing nonradiative recombination, and maintaining considerable stability. The results reveal that the power conversion efficiency (PCE) of the 1.68 eV WBG perovskite solar cell with an inverted structure increases from 18.51% to 21.50%, and the Voc loss is only 0.487 V. The unpackaged device maintains 95% of its initial PCE after 500 h, in an N2 environment at 25 ℃.